Characteristics of Tamarind Seed Biochar at Different Pyrolysis Temperatures as Waste Management Strategy: Experiments and Bibliometric Analysis - Ali Rahmat; Sutiharni Sutiharni; Yetti Elfina; Yusnaini Yusnaini; Hadidjah Latuponu; Faidliyah Nilna Minah; Yeny Sulistyowati; Abdul Mutolib (Universitas Pendidikan Indonesia, 2023)
Household activities and beverage industries that use tamarind often generate waste in the form of tamarind seeds. Tamarind seeds account for approximately 40% of the total weight of the fruit. If these tamarind seeds are not properly managed, they end up as waste with no economic or other benefits. One effective waste management strategy is to convert tamarind seeds into biochar. This research aims to examine the characteristics of biochar produced from tamarind seeds at different pyrolysis temperatures. The results indicate that as the pyrolysis temperature increases, the fixed carbon content also increases. Pores begin to form on the surface of the biochar at a temperature of 400°C. We have identified functional groups such as C-H, O-H, C≡N, C≡C, C=C, C=O, CH3, C-O, and C-C in the biochar. The dominant elements in tamarind seed biochar are K2O, CaO, P2O5, SO3, and MgO, which are part of macronutrients and alkaline elements with the potential to improve soil quality as soil amendments.